THE ROLE OF EDUCATION IN EMPOWERING WOMEN IN SUMATRA UTARA - Adam Syahdani; Grace Yolanda Panjaitan; Hijryah Lativa Sihombing; Laila Azizah Lubis; Meisuri, Meisuri (Cahaya Ilmu Bangsa Institute, 2024)
Education serves as a powerful tool for women's empowerment, driving personal growth, social change, and economic progress. It equips women with the necessary knowledge and skills to access opportunities, make informed decisions, and actively engage in society. In many regions, including North Sumatra, Indonesia, historical cultural norms and economic challenges have limited women's educational access. However, as global awareness of gender equality rises, initiatives to close the gender education gap have increased. Education not only promotes gender equality but also produces numerous positive externalities, such as delayed marriage, reduced fertility rates, increased labor force participation, and improved health outcomes for women and their families. Women’s empowerment through education is not merely about ensuring access; it also emphasizes the quality and relevance of education. Educated women break cycles of poverty, gain leadership roles, and strengthen their communities. However, they still face significant barriers, such as cultural restrictions and economic hardships. These obstacles, particularly in rural areas, prevent many women from reaching their educational potential. Despite these challenges, the empowerment of women through education in regions like North Sumatra is vital for both individual and societal advancement. Continued investment in education for women is essential, not only as a matter of equality but as a crucial driver of sustainable development and societal progress.